Cultural practices of breast care among breastfeeding mothers in the Sumba tribe: A descriptive qualitative study - Tarapandjang, Dharma Sandi; Trishinta, Sirli Mardianna; Ardiyani, Vita Maryah (Universitas Airlangga, 2024)
Introduction: The study aims to explore how the cultural practice of breast care among breastfeeding mothers in the Sumba tribe, specifically in Kiritana Village, might impact the promotion of exclusive breastfeeding in the Nusa Tenggara Timur (NTT) province, with a potential influence estimated at 62.17%.Methods: This research employs a descriptive qualitative approach, utilizing a purposive sampling method. The participants consist of mothers who are within the first six months postpartum and engage in breast care practices. Following the framework proposed by Miles and Huberman, the data analysis process involves data reduction, data display, and drawing conclusions or verifying the data through researcher involvement in the interpretation process to elucidate the significance of the presented data.Results: There are two themes emerged: (1) Culture-based breast care of the Sumba Tribe in Kiritana Village is still being carried out from generation to generation, and (2) Cultural-based breast care practices in the Sumba Tribe, Kiritana Village which is still carried out by breastfeeding mothers are massaged using breastmilk, massaged using coconut oil, herbs which derived from plants and consuming fried corn and fried peanuts.Conclusions: Sumbanese people in Kiritana Village believe that cultural-based breast care can facilitate breast milk and can cure several diseases of the breast, such as sore nipples and swollen, stiff, and hard breasts. It is recommended that health service workers carry out a culture-based approach strategy to the problem of breastfeeding mothers in the Sumba Tribe. Further research on the effects of traditional treatments during postpartum, especially for breast care, is recommended. Keywords: breast care; cultural practice; exclusive breastfeeding